PENGAJARAN MIKRO SUATU PENDEKATAN MENUJU GURU PROFESIONAL - Nurlaila Nurlaila (Ta'dib, 2009)
Microteaching plays very important roles in preparing (candidate) teachers to become professional since through practices on microteaching approach, basic teaching skills can be fully understood and practiced by the candidate teachers. Consequently, the teachers can achieve the effectiveness of teaching, that is, the accomplishment of goals and satisfactory learning outcomes.Kata kunci: pengajaran mikro, keterampilan dasar mengajar, guru profesional